2022
DOI: 10.21873/cdp.10171
|View full text |Cite
|
Sign up to set email alerts
|

Profile and Potential Significance of Dendritic Cells in Head and Neck Squamous Cell Carcinoma

Abstract: Background/Aim: The aim of the study was the analysis of immunohistochemical expression of S100 protein and CD1a by dendritic cells (DCs) from head and neck squamous cell carcinoma (HNSCC), correlation with the histological grade, as well as analysis of the potential significance of antigen-presenting cells according to tumor location. Patients and Methods: Samples were collected from 50 patients with HNSCC, conventionally stained with hematoxylin and eosin for pathological diagnosis and grade, followed by imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…In a previous study conducted in our laboratory, CD1a-DCs were found to be associated with unfavorable clinical outcomes in patients with advanced laryngeal cancer who had undergone total laryngectomy as the initial treatment [23]. However, only a small number of studies have focused on DC infiltration into laryngeal cancer tissue, but the results differed [24][25][26][27][28][29]; thus, the role of DC infiltration in laryngeal cancer remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study conducted in our laboratory, CD1a-DCs were found to be associated with unfavorable clinical outcomes in patients with advanced laryngeal cancer who had undergone total laryngectomy as the initial treatment [23]. However, only a small number of studies have focused on DC infiltration into laryngeal cancer tissue, but the results differed [24][25][26][27][28][29]; thus, the role of DC infiltration in laryngeal cancer remains unclear.…”
Section: Introductionmentioning
confidence: 99%